(untitled) (Research, Society and Development, 2021)
Introduction: According to the WHO (World Health Organization) it is estimated that in Brazil 12 million people (around 5.8% of the population) suffer from depression and consequently acquire anxiety. clinical presentation is aggravated by the lack of knowledge on the theme and by the lack of resources for the proper treatments, unfortunately the treatment methods are still extremely invasive through strong medications. Methodology: This study was based on an exploratory bibliographical research, through a literary research, from the analysis of articles and books on the theme, in the following databases: PunMed, Google academic, Scielo and Pedro, selected in the last 20 years, with the themes of anxiety, depression, massage and acupuncture. Results: Based on this bibliographical study, we prove the effectiveness of physical therapy in the treatment of anxiety and depression, using alternative means such as acupuncture and massage therapy. In the application of such techniques, a decrease in the symptoms of these pathologies has been reported. It is extremely important that the patient understands that medication is not the only form of treatment. Final considerations: We can conclude that despite being little mentioned, alternative treatments for depression and anxiety are effective, as long as they are applied and prescribed by qualified professionals.